The Global Dominance of English Language in Homeopathic Research: A Double-Edged Sword (Advancements in Homeopathic Research, 2025)
The English language has many positive aspects,  such as its wide acceptance, its reputation as an  academic language, and the ability to offer a broad  array of literature in digital and print formats.  Overall, like many other disciplines, there are  various advantages to the widespread use of English  in global collaboration and research dissemination in  homeopathy as it enhances the reach and credibility  of the discipline and equality. The English language's  wide adoption contributes to offering a global forum  for the exchange of innovative concepts and scientific  discoveries, which can promote a more diverse  and robust international research environment  in Homoeopathy. Conversely, it is imperative to  acknowledge and tackle the constraints, difficulties,  and possible prejudices that come with using of the  English language. The predominance of English may  suggest that studies conducted in countries where  the language is not spoken have been overlooked,  which could result in a bias and a gap in scientific  understanding.
Keywords: English Language; Global Dominance; Homeopathic Research